The potential of mesenchymal stem‐cell secretome for regeneration of intervertebral disc: A review article - Cita Rosita Sigit Prakoeswa; Damayanti Tinduh; Hari Basuki Notobroto; Fedik Abdul Rantam; Dwikora Novembri Utomo; Heri Suroto; Ferdiansyah Ferdiansyah; Romaniyanto Romaniyanto (Universitas Gadjah Mada, 2021)
Low back pain is a crucial public health problem that is commonly associated with intervertebral disc de‐ generation and has vast socio‐economic impact worldwide. Current treatments for disc degeneration are conservative, non‐surgical, or surgical interventions, and there is no current clinical therapy aimed at directly reversing the degeneration. Given the limited capacity of intervertebral disc (IVD) cells to self‐repair, treatment aiming to regenerate IVDs is a topic of interest and mesenchymal stem cells (MSCs) have been identified as having potential in this regeneration. Recent studies have revealed that the benefits of MSC therapy could result from the molecules the cells secrete and that play principal roles in regulating essential biologic processes, rather than from the implanted cells themselves. Therefore, the objective of this study is to review the potential use of the MSC secretome to regenerate IVDs. Current evidence shows that the secretome may regenerate IVDs by modulating the gene expressions of nucleus pulposus cells (upregulation of keratin 19 and downregulation of matrix metalloproteinase 12 and matrix Gla protein) and stimulating IVD progenitor cells to repair the degenerated disc.